2023
DOI: 10.3390/ijms24065595
|View full text |Cite
|
Sign up to set email alerts
|

Odorant-Binding Proteins and Chemosensory Proteins in Spodoptera frugiperda: From Genome-Wide Identification and Developmental Stage-Related Expression Analysis to the Perception of Host Plant Odors, Sex Pheromones, and Insecticides

Abstract: Spodoptera frugiperda is a worldwide generalist pest with remarkable adaptations to environments and stresses, including developmental stage-related behavioral and physiological adaptations, such as diverse feeding preferences, mate seeking, and pesticide resistance. Insects’ odorant-binding proteins (OBPs) and chemosensory proteins (CSPs) are essential for the chemical recognition during behavioral responses or other physiological processes. The genome-wide identification and the gene expression patterns of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 103 publications
(121 reference statements)
0
15
0
Order By: Relevance
“…We found that the odorant-binding protein (OBP) genes were under strong selection. The OBP is involved in the regulation of insect host recognition, foraging, courtship, and other behaviors [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that the odorant-binding protein (OBP) genes were under strong selection. The OBP is involved in the regulation of insect host recognition, foraging, courtship, and other behaviors [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…OBPs can transport chemicals to odorant receptors (ORs), which comprise the first step in insect olfactory molecule recognition [ 44 ]. As demonstrated here and in prior publications, OBP functions can be delineated through a combination of fluorescence competition binding, EAG assays, and RNA interference (RNAi) [ 45 ]. For example, Bradysia odoriphaga shows strong EAG responses to the host plant volatiles methyl allyl disulfide and diallyl disulfide.…”
Section: Discussionmentioning
confidence: 99%
“…Research on bactericidal and insect properties heavily relies on the ability to identify chemicals that smell green. Prospective green odorants could be applied to forest preservation and agricultural production as fungicidal repellents [ 20 ]. The identification of more green odorant-molecules will greatly advance the study of insects, as green odorants have the potential to function as insect pheromones.…”
Section: Introductionmentioning
confidence: 99%